Report on Survey among interdisciplinary and transdisciplinary researchers and post-survey interviews with policy stakeholders - Spaapen, Jack; Vienni Baptista, Bianca; Buchner, Anna; Pohl, Christian (My University, 2020)
Through a qualitative survey among European researchers and interviews with policy makers we hope to enhance knowledge about interdisciplinary and transdisciplinary collaboration. The survey and interviews were carried out as part of Work Package 2 of the SHAPE-ID Horizon 2020 project (https://www.shapeid.eu), which is also conducting a systematic literature review. We aim to serve the research community and relevant stakeholders in society with new insights, examples of good practice and tips on how to overcome difficulties that might help their current and future interdisciplinary and transdisciplinary endeavours. We focus on Arts, Humanities and Social Sciences (AHSS), but are also interested in the growing collaboration between these fields and the so-called STEMM fields (Science, Technology, Engineering, Medicine and Mathematics). We address two main questions: (i) When developing a European interdisciplinary or transdisciplinary project, what are the main difficulties people encounter in realising a good research team that is balanced in terms of the various interests and goals of the different participants, and (ii) Which factors of success and failure do researchers integrating AHSS in larger projects consider relevant for their daily practice of interdisciplinary and transdisciplinary research?
Keywords: Interdisciplinarity; transdisciplinarity; interdisciplinary research; transdisciplinary research; arts; humanities; social sciences; integration; research policy; research funding; science policy; International Integration; Interdisciplinary research; RESEARCH POLICY IMPLICATIONS; interdisciplinary collaboration; transdisciplinary collaboration